Peningkatan Hasil Belajar Siswa Kelas 2 pada Mata Pelajaran PKN Materi Pancasila dengan Metode Demonstrasi - Maidah, Maidah; Miftachudin, Miftachudin; Muttaqin, Muhammad Fauzan (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2024)
The aim of this research is to determine the improvement in student learning outcomes in PKN learning Pancasila material using the demonstration method for class II at SD DAQU Internasional Tangerang. This research is classroom action research (PTK). The subjects of this research were 25 class II students. Data collection techniques were carried out using observation, test and documentation methods. The PTK model uses 2 cycles, each cycle consisting of 4 stages, namely, 1) Action Plan 2) Implementation 3) Observation 4) Reflection. Data analysis techniques use student data, namely planning data, implementation data, observation data and reflection data. The research results showed that the formative test results obtained by students in the pre-cycle of 25 students only 14 students (56%) completed. In Cycle I the results were 18 students (72%) who completed. In cycle II, students' formative test results increased to 23 students (92%) who completed it. Meanwhile, 2 students who got a score of less than 70 were declared incomplete and needed to carry out follow-up action in the form of giving assignments. So that the use of the demonstration method can improve student learning outcomes in civics subjects with Pancasila material using the demonstration method for class II elementary school.